Maximum isometric muscle strength as a predicror of one repetition maximum in the squat test - Borko Petrović; Aleksandar Kukrić; Radenko Dobraš; Nemanja Zlojutro (University of Banja Luka, Faculty of physical education and sport, 2020)
This study aims to determine whether maximum isometric muscle strength, exerted at a certain angle in the knee joint (80 °, 110 °, and 140 °), may be used as a predictor of 1RM in the squat movement task. A group of twenty-four male students (N = 24) took part in the research in 2 separate sessions and 7 days of rest between each. In the first session, the anthropometric measurements and assessment of muscle strength, that is 1RM, were measured by maximum repetition to failure method on the Smith machine. The maximum isometric force (Fmax) of the leg muscles was measured by the Alternating Consecutive Maximum Contraction Test in laboratory conditions on a Smith machine using a dynamometer probe and the Globus Ergo Tesys System 1000 software system. Analyzing the results based on linear regression, the authors conclude that, with an accuracy of 84.5%, we can estimate 1RM in the squat exercise measuring the maximum isometric force exerted at an angle in the knee joint of 140 °. The results obtained by this research can be used in practice when assessing 1 RM based on the measurement of the maximum isometric force for a given movement task.